Package relation-well-founded: Well-founded relations
Information
name | relation-well-founded |
version | 1.47 |
description | Well-founded relations |
author | Joe Leslie-Hurd <joe@gilith.com> |
license | MIT |
requires | bool pair relation-def relation-thm |
show | Data.Bool Data.Pair Relation |
Files
- Package tarball relation-well-founded-1.47.tgz
- Theory file relation-well-founded.thy (included in the package tarball)
Defined Constant
- Relation
- wellFounded
Theorems
⊦ wellFounded empty
⊦ ∀r. wellFounded r ⇒ irreflexive r
⊦ ∀r s. subrelation r s ∧ wellFounded s ⇒ wellFounded r
⊦ ∀r m. wellFounded r ⇒ wellFounded (λx y. r (m x) (m y))
⊦ ∀r. wellFounded r ⇔ ∀p. (∀x. (∀y. r y x ⇒ p y) ⇒ p x) ⇒ ∀x. p x
⊦ ∀r. wellFounded r ⇔ ∀p. (∃x. p x) ⇔ ∃x. p x ∧ ∀y. r y x ⇒ ¬p y
⊦ ∀r. wellFounded r ⇔ ∀p. (∃x. p x) ⇒ ∃x. p x ∧ ∀y. r y x ⇒ ¬p y
⊦ ∀r s.
wellFounded r ∧ wellFounded s ⇒
wellFounded (λ(x1, y1) (x2, y2). r x1 x2 ∧ s y1 y2)
⊦ ∀r s.
wellFounded r ∧ wellFounded s ⇒
wellFounded (λ(x1, y1) (x2, y2). r x1 x2 ∨ x1 = x2 ∧ s y1 y2)
⊦ ∀r s.
wellFounded r ∧ (∀a. wellFounded (s a)) ⇒
wellFounded (λ(x1, y1) (x2, y2). r x1 x2 ∨ x1 = x2 ∧ s x1 y1 y2)
Input Type Operators
- →
- bool
- Data
- Pair
- ×
- Pair
Input Constants
- =
- select
- Data
- Bool
- ∀
- ∧
- ⇒
- ∃
- ∨
- ¬
- ⊥
- ⊤
- Pair
- ,
- Bool
- Relation
- empty
- irreflexive
- subrelation
Assumptions
⊦ ⊤
⊦ ¬⊥ ⇔ ⊤
⊦ ¬⊤ ⇔ ⊥
⊦ ∀t. t ⇒ t
⊦ ⊥ ⇔ ∀p. p
⊦ ∀t. t ∨ ¬t
⊦ (¬) = λp. p ⇒ ⊥
⊦ ∀t. (∀x. t) ⇔ t
⊦ ∀t. (∃x. t) ⇔ t
⊦ ∀t. (λx. t x) = t
⊦ (∀) = λp. p = λx. ⊤
⊦ ∀t. ¬¬t ⇔ t
⊦ ∀t. (⊤ ⇔ t) ⇔ t
⊦ ∀t. ⊥ ∧ t ⇔ ⊥
⊦ ∀t. ⊤ ∧ t ⇔ t
⊦ ∀t. t ∧ ⊤ ⇔ t
⊦ ∀t. ⊥ ⇒ t ⇔ ⊤
⊦ ∀t. ⊤ ⇒ t ⇔ t
⊦ ∀t. t ⇒ ⊤ ⇔ ⊤
⊦ ∀t. ⊥ ∨ t ⇔ t
⊦ ∀t. ⊤ ∨ t ⇔ ⊤
⊦ ∀t. t ∨ ⊤ ⇔ ⊤
⊦ ∀x y. ¬empty x y
⊦ ∀t. (⊥ ⇔ t) ⇔ ¬t
⊦ ∀t. t ⇒ ⊥ ⇔ ¬t
⊦ (⇒) = λp q. p ∧ q ⇔ p
⊦ ∀t. (t ⇔ ⊤) ∨ (t ⇔ ⊥)
⊦ ∀p x. p x ⇒ p ((select) p)
⊦ ∀f y. (let x ← y in f x) = f y
⊦ ∀t1 t2. t1 ∧ t2 ⇔ t2 ∧ t1
⊦ ∀t1 t2. t1 ∨ t2 ⇔ t2 ∨ t1
⊦ ∀r. irreflexive r ⇔ ∀x. ¬r x x
⊦ (∧) = λp q. (λf. f p q) = λf. f ⊤ ⊤
⊦ ∀p. ¬(∀x. p x) ⇔ ∃x. ¬p x
⊦ ∀p. ¬(∃x. p x) ⇔ ∀x. ¬p x
⊦ (∃) = λp. ∀q. (∀x. p x ⇒ q) ⇒ q
⊦ ∀t1 t2. ¬(t1 ⇒ t2) ⇔ t1 ∧ ¬t2
⊦ ∀t1 t2. ¬t1 ⇒ ¬t2 ⇔ t2 ⇒ t1
⊦ ∀p. (∀xy. p xy) ⇔ ∀x y. p (x, y)
⊦ (∨) = λp q. ∀r. (p ⇒ r) ⇒ (q ⇒ r) ⇒ r
⊦ ∀f. ∃fn. ∀x y. fn (x, y) = f x y
⊦ ∀p q. p ∧ (∃x. q x) ⇔ ∃x. p ∧ q x
⊦ ∀p q. p ⇒ (∀x. q x) ⇔ ∀x. p ⇒ q x
⊦ ∀p q. p ∨ (∀x. q x) ⇔ ∀x. p ∨ q x
⊦ ∀p q. p ∨ (∃x. q x) ⇔ ∃x. p ∨ q x
⊦ ∀p q. (∃x. p x) ⇒ q ⇔ ∀x. p x ⇒ q
⊦ ∀p q. (∃x. p x) ∨ q ⇔ ∃x. p x ∨ q
⊦ ∀t1 t2 t3. (t1 ∨ t2) ∨ t3 ⇔ t1 ∨ t2 ∨ t3
⊦ ∀p. (∀x. ∃y. p x y) ⇔ ∃y. ∀x. p x (y x)
⊦ ∀r s. subrelation r s ⇔ ∀x y. r x y ⇒ s x y